Lead and mercury exposure in populations on the banks of the bogotá river: A multi-method study (2019)
Objectives This study sought to understand the health problems associated with the presence of lead and mercury in the water of the Bogotá River. Materials and Methods A mixed methods study was conducted using interviews, surveys and measurements of zinc protoporphyrin (ZPP) and mercury in blood from 172 individuals. Variables associated with the highest concentrations were identified, as well as the attributes of the cases with increased exposure by means of a qualitative comparative analysis. Results Interviews reported that river pollution is associated with diseases, although direct exposure to water is rare. River water is widely used for irrigation of crops that are sold in other municipalities. Communities with greater exposure to river water are Tocaima and Girardot. The highest levels of ZPP were observed among those living in these municipalities, did activities at home and performed non-work activities using metals. Increased ZPP levels were associated with depression, nasal bleeding and loss of appetite. The highest concentrations of mercury were found in the inhabitants of Girardot, and were associated with sweating, disorientation, nausea and diarrhea. Conclusion Low levels of lead and mercury were observed in the study population, although there are specific cases with high social vulnerability that require special attention. © 2019, Universidad Nacional de Colombia. All rights reserved.